2016
DOI: 10.1016/j.ijrobp.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Local Control With 21-Gy Radiation Therapy for High-Risk Neuroblastoma

Abstract: Purpose The optimal dose of radiation in high-risk neuroblastoma is unknown. We sought to evaluate local control following 21-Gy radiotherapy (RT) to the primary site in patients with high-risk neuroblastoma. Patients and Methods After receiving dose-intensive chemotherapy and gross total resection (GTR), 246 patients (ages 1.2–17.9, median 4.0 years) with high-risk neuroblastoma underwent RT to the primary site at xxx from 2000–2014. RT consisted of 21 Gy in twice-daily fractions of 1.5 Gy each. Local failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…All patients had undergone chemotherapy before RT, as previously described (11). The systemic therapy exposures are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…All patients had undergone chemotherapy before RT, as previously described (11). The systemic therapy exposures are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Local control is inherently a part of curative therapy, and RT following surgical resection is a necessary component. Radiation therapy is most commonly tasked with controlling microscopic disease, because GTR is achievable in the majority of cases, and for this purpose, RT doses between 21 and 24 Gy seem to be effective (4, 69, 11, 22). Historically, consensus favored improved outcomes with either greater than 90% resection or GTR (2326), though other authors have found no relation to extent of resection (5, 2729), leaving uncertainty regarding how to compensate when residual tissue remains.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfractionation (9, 12) and proton therapy (33) have also been means by which attempts have been made to mitigate late toxicities. With the sort of radiosensitivity that our series and others suggest, allowing for most RT courses to be limited to 21.6 Gy, it may be that modern, more-expensive techniques would practically provide no clinical advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Our institution and others have previously shown that a dose of 21 Gy RT provides excellent local control after gross total resection (GTR). [4][5][6][7] Although local failure (LF) is <10% among patients treated with 21 Gy RT after GTR, locoregional recurrence is much Abbreviations: CTV, clinical target volume; EFS, event-free survival; GTR, gross total resection; LF, local failure; MSK, Memorial Sloan Kettering; OS, overall survival; RT, radiation therapy more common among patients with macroscopic residual disease after surgical resection, with local recurrence rates approaching 50%. 8 There are no randomized trials that have directly addressed the role and optimal dose of RT to the primary site in high-risk neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%